Comparative analyses of salivary exosomal miRNAs for patients with or without lung cancer - Liu, Mengfeng; Yu, Xiran; Bu, Jianlong; Xiao, Qifan; Ma, Sitong; Chen, Naozhong; Qu, Changfa (Frontiers in Genetics, 2023)
Lung cancer is the most frequent cause of cancer-related deaths worldwide.Exosomes are involved in different types of cancer, including lung cancer. We collected saliva from persons with (LC) or without (NC) lung cancer, and successfully isolated salivary exosomes by ultracentrifugation. The miRNA sequencing was implemented for the exosome samples from NC and LC groups, and a total of 372 miRNAs were found. Subsequently, 15 differentially expressed(DE) miRNAs were identified in LC vs NC, including 8 upregulated and 7 downregulated miRNAs. Some DE miRNAs were validated by quantitative real time polymerase chain reaction (qPCR). A total of 488 putative target genes of the upregulated DE miRNAs were found, and the functional analyses indicated that numerous target genes were enriched in the pathways associated with cancer, suggesting that miRNAs of salivary exosomes might have the potential to be used as biomarkers for prediction and diagnosis of lung cancer.